Strategi Guru Pendidikan Agama Islam dalam Mengatasi Kesulitan Peserta Didik Membaca Al Qur'an di Kelas XI SMA Negeri 1 Kecamatan Guguak - Jannatul Asrari; Ahmad Kosasih (AS-SABIQUN, 2022)
In the 21st century, there are still many students who have difficulty in reading the Qur'an. This study aims to identify the difficulties of students reading the Qur'an, strategies and factors that encourage and inhibit PAI teachers in overcoming the difficulties of students reading the Qur'an at SMA Negeri 1 Kec. Guguak. This research method uses qualitative methods and case study research types. The data sources in this study were PAI students and teachers of class XI SMA Negeri 1 Kec. Guguak and data collection through interviews, observation and documentation using purposive sampling technique. The results of the study were the difficulties of students, namely Makhorijul letters, the law of reading Nun Sukun and Mim Sukun and short length (Mad wal Qashar). The PAI teacher's strategy to overcome this is a) Maximizing 15-20 minutes of reading the Qur'an before starting learning, b) Giving assignments c) Using lecture and practice methods (Drilling Method). Supporting factors for PAI teachers are the teacher's personal desire to improve student reading and well-managed facilities such as classrooms and prayer rooms. The inhibiting factors are a) lack of awareness of students, b) lack of school support, c) lack of attention from parents. The results of the study can be used as a reference for further research related to the difficulty of reading the Qur'an.